2020
DOI: 10.34172/ijer.2020.23
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pomegranate Peel Extract and Vitamin E on Quality of Life in Hemodialysis Patients: A Randomized Placebo-Controlled Clinical Trial

Abstract: Background and aims: Quality of life (QOL) is poor in hemodialysis (HD) patients. High oxidative stress and inflammatory conditions disturb their normal physiological, emotional, and physical functions. This study aimed to assess the effects of pomegranate peel extract (PPE) alone and in combination with vitamin E (Vit E) as anti-oxidant and anti-inflammatory substances on QOL of HD patients using Short-form 36 (SF-36) QOL questionnaire. Methods: This study was a double-blinded, placebo-controlled randomized c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…These aspects may affect our results. However, according to a study by Jafari et al, vitamin E supplementation had a positive correlation with improving the quality of life in hemodialysis patients, particularly in mental components (45).…”
Section: Correspondi Ng Capsules 4 Months Crpmentioning
confidence: 97%
“…These aspects may affect our results. However, according to a study by Jafari et al, vitamin E supplementation had a positive correlation with improving the quality of life in hemodialysis patients, particularly in mental components (45).…”
Section: Correspondi Ng Capsules 4 Months Crpmentioning
confidence: 97%
“…Several studies have reported an improvement in quality of life after consumption of Golnar product and its components [ 18 , 20 , 21 , 23 , 29 ]. Other studies also demonstrated that pomegranate peel extract or supplements could improve the quality of life of hemodialysis patients and menopausal women [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%